Mechanical Behaviours and Thermal Stabilities of Irradiated Epoxidized Natural Rubber/Polyvinyl Chloride/Carbon Nanotubes Nanocomposites - Mohd Shahrulnizam Ahmad; Zurina Mohamad; Chantara Thevy Ratnam; Norhayani Othman; Roshafima Rasit Ali (Chemical Engineering Transactions, 2022)
The effects of carbon nanotubes addition (nanotube contents and functionalized MWNTs) and also irradiation modification on the mechanical behaviours and thermal stabilities of epoxidized natural rubber (ENR-50)/poly (vinyl chloride) (PVC)/multi-walled carbon nanotubes (MWNTs) nanocomposites were investigated. ENR-50/PVC/MWNTs nanocomposites were prepared by melt mixing in a Brabender Plastigraph at 150 °C with a rotor speed of 50 rpm followed by compression molding at 160 °C. The samples were irradiated in a 2 MeV electron beam (EB) machine at a dose of 200 kGy. The dynamic mechanical properties and glass transition temperature properties of the resulting composites were investigated as a function of MWNTs contents, functionalized MWNTs, and irradiation dose. The storage modulus and glass transition temperature (Tg) increased by increasing nanotube content (0 to 8 phr) at 0 kGy and further increased after being irradiated with 200 kGy. Moreover, this is inversely proportional to loss modulus and can be seen that loss modulus decreased with the addition of nanotube content. In the aspect of functionalization effects, MWNTs-COOH recorded higher Tg at 0 kGy and MWNTs-OH at 200 kGy. However, results for storage modulus by the effect of functionalization totally dropped as compared with ENR-50/PVC and ENR-50/PVC/MWNTs blends. This showed that the storage modulus is not proportional to the increase of Tg and also the loss modulus.